1996
DOI: 10.3109/00016489609137705
|View full text |Cite
|
Sign up to set email alerts
|

Distortion Product Otoacoustic Emission Test of Sensorineural Hearing Loss: Performance Regarding Sensitivity, Specificity and Receiver Operating Characteristics

Abstract: The performance of distortion product otoacoustic emissions (DPOEs) as a frequency-specific test of sensorineural hearing loss was evaluated in 142 ears of human adults with normal middle-ear function. The DPOE was measured with the stimulus levels of the two tones equal to 65 dB SPL (re 20 mu Pa) and the ratio between the two frequencies 1.2. In the DPOE test, the cochlear function of an ear at a test frequency was predicted to be normal or abnormal depending upon whether the DPOE level with the geometric mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 18 publications
4
42
1
Order By: Relevance
“…Bonfils et al (1994) used fixed stimulus intensity of 52 dB SPL in 102 ears and found a sensitivity of 0.93 for predicting hearing loss greater than 25 dB HL at 2 kHz. Gorga (1993) reported similar results, while Kim, (1996) using higher stimulus intensities of 65 dB SPL, found a lower sensitivity of 82%. Kimberley et al (1994a) used discriminant analysis and claimed a prediction accuracy of 92% at 2000 Hz.…”
Section: Discussionsupporting
confidence: 77%
“…Bonfils et al (1994) used fixed stimulus intensity of 52 dB SPL in 102 ears and found a sensitivity of 0.93 for predicting hearing loss greater than 25 dB HL at 2 kHz. Gorga (1993) reported similar results, while Kim, (1996) using higher stimulus intensities of 65 dB SPL, found a lower sensitivity of 82%. Kimberley et al (1994a) used discriminant analysis and claimed a prediction accuracy of 92% at 2000 Hz.…”
Section: Discussionsupporting
confidence: 77%
“…Thus, the results at 4 kHz indicate more variability and, therefore, more frequent occurrence of standing-wave effects at this frequency (compared to the other four octave frequencies). Despite the fact that variability is greater at 4 kHz, DPOAE test performance (identifying normal and impaired ears) is best at this frequency (e.g., Gorga et al, 1993Gorga et al, , 1997Kim et al, 1997;Johnson et al,. 2010;Burke et al, 2010).…”
Section: B Distribution Of Magnitude Differencesmentioning
confidence: 99%
“…This approach, which is well suited to assessing the accuracy with which diagnostic tests provide dichotomous classifications (i.e., normal or impaired hearing in the present case), has been used previously to evaluate DPOAE test performance (e.g., Gorga et al, 1993Gorga et al, , 1997Gorga et al, , 1999Gorga et al, , 2000Gorga et al, , 2005Kim et al, 1996;Stover et al, 1996a;Dorn et al, 1999). In these applications of CDT, audiometric threshold served as the gold standard to which the results from the experimental measurement (typically DPOAE level) were compared.…”
Section: A Accuracy Of the Dichotomous Decisionmentioning
confidence: 99%